The Philosophy of the Imagination in Vico and Malebranche - Paolo, Fabiani (Strumenti per la didattica e la ricerca, 2009)
This book is a retrospective view of modern philosophical anthropology through the works of two of its greatest exponents. the author demonstrates how mythology, the philosophy of history and language and Vico's concept of man had as a constant referral point Malebranche's psychology with its Cartesian formulation. The idolatrous and mythopoietic imagination that is described in La Scienza Nuova (New Science) has much in common with the "pagan" mind (that is to say the mind subjugated to passions, sensitivity and fantasy that is described in La Recherche (The Search after Truth). Some of the themes discussed here are myth, the metaphoric nature of thought, idolatry, the formation of mentality, the relationships which bind passions and representations and the association of ideas through iconic images. Also discussed are other themes such as the structure of society and imagination, imitation, persuasion and social relationships, communication within society between illustrious imaginations. Moreover in Malebranche has been found a complex and complete theory of imaginative universals (universali fantastici).